Hubungan Waktu Tunggu Pendaftaran Dengan Kepuasaan Pasien Di Tempat Pendaftaran Pasien Rawat Jalan (TPPRJ) RSUD Sukoharjo - Dewi, Utami Aulia; , dr. Rukma Astuti., MPH; , Kusuma Estu Werdani, SKM., M.Kes (2015)
The improvement of quality of service is the most priority in hospital management. Basically,each hospital is developed to attain the customers satisfaction it is also happened in RSUD Sukoharjo. Outpatient Registration site (TPPRJ) is the first service as the hospital gate, which is crucial site to give the first impression. The waiting time in TPPRJ is one of the important things that determine the initial image of the hospital. This study aimed to analyze the correlation between waiting time of registration with patient satisfaction in TPPRJ RSUD Sukoharjo. The type of this research was analytic observational with cross sectional approach. The research instrument were questionnaire and observation sheet. The population in this study were all outpatients who registered to TPPRJ RSUD Sukoharjo. The sampling technique used quota sampling which was the total samples were 95 respondents. The data were analyzed by using Chi Square test. The results showed that there was a relation between the waiting time of registration with patient satisfaction in TPPRJ RSUD Sukoharjo (p = 0,000) with OR = 15,944.